Diffractive electromagnetic processes from a Regge point of view - Dosch, Hans Günter; Ferreira, Erasmo (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The energy dependence of the cross sections for electromagnetic diffractive processes can be well described by a single power, Wδ. For J/ψ photoproduction this holds in the range from 20 GeV to 2 TeV. This feature is most easily explained by a single pole in the angular momentum plane which depends on the scale of the process, at least in a certain range of values of the momentum transfer. It is shown that this assumption allows a unified description of all electromagnetic elastic diffractive processes. We also discuss an alternative model with an energy-dependent dipole cross section, which is compatible with the data up to 2 TeV and which shows an energy behavior typical for a cut in the angular momentum plane.
Gesehen am 25.06.2020